Filsafat Ilmu sebagai Landasan Pengembangan Pendidikan Bahasa - Donny Adiatmana Ginting; M. Zaim; Harris Effendi Thahar (Journal on Education, 2023)
As the mother of knowledge, philosophy of science plays a crucial role in the development of science, particularly language education, which is a subfield of science. This study's objective is to examine language instruction in terms of three facets of the philosophy of science: anthology, epistemology, and axiology. The research approach employs a systematic literature review (SLR) to identify research publications pertinent to the research questions and objectives. Following the screening phase, five research articles that are pertinent to the research questions and objectives enter the analysis and study outcomes phases. According to the study's findings, the ontology component of education stresses the objectives of language instruction, which include core competencies, basic competencies, attitudes, knowledge, and abilities. The epistemological part focuses on language-teaching techniques that prioritize student needs. The axiological part of language learning focuses more on practical values, allowing pupils to effectively communicate following language acquisition. To ensure the continued survival of language education as a science, it is imperative that the development of language education adhere to the ontology, epistemology, and axiology characteristics that are central to the philosophy of science.